The crisis of Muslim religious discourse the necessary shift from Plato to Kant - Addi, Lahouari 1949-; Einsiedel, Bonnie (London New York Routledge, Taylor & Francis, 2022)
Foreword -- Introduction -- 1. Plato and Plotinus in Medieval Abrahamic Theology -- 2. Islam and the Platonic Dualism -- 3. From Sufism to Islamism -- 4. Muhammad Abduh or the Failure of the Epistemic Transition -- 5. A Positivism Without Human Agency -- 6. Transcendence, History and Ethics: Contemporary Stakes -- 7. Shariʻa, Fiqh and Muslim Law -- 8. Europe, Islam and Secularization -- Conclusion -- Appendix: The Debate over the "Secularization Theorem": Carl Schmitt, Karl Löwith, Hans Blumenberg.
"Showing that Muslim societies are facing a crisis that is more cultural than religious, this book focuses on cultural representations through which social life is experienced in the Muslim world. It brings a new theoretical framework to address the secularization process that is underway and the contradictions it entails. This volume will arouse a new debate on secularization and the relations between religion, culture and philosophy. The crisis Muslim societies are undergoing pertains to the culture and not to the Qur'an to the extent that people do not have access to the sacred in itself but only for oneself, meaning a cultural interpretation of the sacred. The Qur'an in itself is not an obstacle to secularization and modernization since any sacred text is experienced through culture. If we consider the European experience where secularization has first emerged, we see that culture has been transformed from medieval metaphysics to modern philosophy upholding a civic culture. Discussing secularization through cultural representation, this book launches new ideas that fill an important gap in the literature on secularization. It is a key resource for any readers interested in religious studies, philosophy and the anthropology of religion"--
Includes bibliographical references and index
Translated from French
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Islam and secularism -- 21st century; Islam and culture -- 21st century; Islamic civilization -- 21st century; Islam and secularism -- History -- 21st century; Islam and culture -- History -- 21st century; Islamic civilization -- History -- 21st century